Characteristics of Extended-Spectrum β-Lactamase–Producing Escherichia coli From Dogs and Cats Admitted to a Veterinary Teaching Hospital in Taipei, Taiwan From 2014 to 2017 - Huang, Yi-Hsuan; Kuan, Nan-Ling; Yeh, Kuang-Sheng (Frontiers in Veterinary Science, 2020)
Extended-spectrum β-lactamases (ESBLs) are enzymes that mediate resistance to newer β-lactam antibiotics, including extended-spectrum cephalosporins and monobactams. The production of ESBL is primarily plasmid mediated, and such plasmids often comprise the genes that encode resistance to other classes of antimicrobials, such as aminoglycosides and fluoroquinolones. Therefore, ESBL-producing microorganisms leave clinicians with limited therapeutic options in both human and veterinary medicine. Compared with human medicine, information regarding ESBL-producing microorganisms is limited in veterinary medicine. We screened for ESBL-producing Escherichia coli in dogs and cats admitted to National Taiwan University Veterinary Hospital, Taipei, from 2014 to 2017 and further analyzed the genotypes and phylogenetic traits of these ESBL producers. Double disk tests specified by the Clinical and Laboratory Standards Institute were performed on 283 E. coli isolates and revealed a total of 65 E. coli (54 from dogs and 11 from cats) with the ESBL phenotype (22.8%). blaCTX−M−1group and blaCTX−M−2group were the most commonly identified ESBL gene groups. blaCTX−M−55 was the main ESBL gene within the blaCTX−M−1group, whereas the blaCTX−M−2group contained only blaCTX−M−124. The ESBL-producing E. coli were all resistant to ampicillin. The resistance rate to ceftiofur, doxycycline, enrofloxacin, and ciprofloxacin was 93.8, 73.8, 80, and 78.5%, respectively. Of the antibiotics tested, greater sensitivity to imipenem and gentamicin was noted. Multilocus sequence typing indicated that ST457, ST131, and ST648 were the most common sequence types. Our study identified eight ST131/O25b isolates, which is a global zoonotic clone of public health concern. The major ESBL genes of these clones were blaCTX−M−174 and blaCTX−M−194. Because companion animals such as dogs and cats are in close contact with humans, the characterization of ESBL producers originating from them is crucial from the perspective of both public health and veterinary medicine.